2022
DOI: 10.1002/cjce.24351
|View full text |Cite
|
Sign up to set email alerts
|

Synthesizing magnetic graphene oxide nanomaterial (GO‐Fe3O4) and kinetic modelling of methylene blue adsorption from water

Abstract: Methylene blue (MB) is a frequently used dye in several industries that is detrimental both to human health and aquatic ecosystems. Graphene oxide (GO) has the application potential for dye removal from wastewater due to its high specific surface area; however, it suffers from a labourious separation step. In this work, magnetic GO nanostructure was prepared by co‐precipitation of ferrous salts in presence of GO to achieve a GO‐Fe3O4 hybrid. By choosing the proper ratio of GO to Fe3O4, the specific surface are… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
1
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 56 publications
0
1
0
Order By: Relevance
“…The distance between GO layers and the associated surface area was adjustable by controlling the mass ratio of Fe 3 O 4 to GO in the synthesis of the composite. It has been reported that Fe 3 O 4 strengthened the van der Waals force and π-π interaction between GO layers, preventing aggregation and thus increasing surface area and adsorption capacity [ 21 , 23 ].…”
Section: Introductionmentioning
confidence: 99%
“…The distance between GO layers and the associated surface area was adjustable by controlling the mass ratio of Fe 3 O 4 to GO in the synthesis of the composite. It has been reported that Fe 3 O 4 strengthened the van der Waals force and π-π interaction between GO layers, preventing aggregation and thus increasing surface area and adsorption capacity [ 21 , 23 ].…”
Section: Introductionmentioning
confidence: 99%
“…Nevertheless, several investigations have demonstrated that some undesired SPION aggregates may have lower stability, biocompatibility, and effectiveness. As a result, the use of SPION in conjunction with other stabilizing tools, such as carbon compounds, has been researched [6,10,[17][18][19][20][21][22][23][24][25][26][27][28][29][30][31].…”
Section: Introductionmentioning
confidence: 99%
“…SPION@C using bergamia orange gave good results, with an adsorption of 141.3 mg/g [32]. SPION/GO had the highest ratio with 280.26 mg/g [25]. Since then, a number of material combinations with SPION to improve and enhance some features as well as save costs have also been implemented.…”
Section: Introductionmentioning
confidence: 99%
“…At the nanoscale, superparamagnetism, a unique magnetic feature of ferromagnetic iron oxide, does exist [14][15][16]. Comparing the MB adsorption capacity of SPIONs to SPION@Carbon sheets, SPION/expanded graphite, SPION/GO, and SPION/MWCNT, the adsorption capacity can be 45.43 [17], 95, 76.2 [18], 280.26 [19], and 280.06 mg/g, respectively [20].…”
Section: Introductionmentioning
confidence: 99%